Answer with Step-by-step explanation:
we are given a equation
![√(x+8)-6=x](https://img.qammunity.org/2019/formulas/mathematics/middle-school/a5imkx966g2lgfots1hfr1sgbx5vpa2kg8.png)
add 6 to both sides
![√(x+8)=x+6](https://img.qammunity.org/2019/formulas/mathematics/middle-school/bfshfrmiea7qbz9mehqaq91z3hnmfaiqs1.png)
squaring both sides
![x+8=(x+6)^2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/m0680sk4le2mnp9pzgus87gcm0jqfn3069.png)
x+8 = x² + 12x +36
subtract x from the both sides
8 = x² + 11x + 36
subtract 8 from both sides
0 = x² + 11x + 28
or x²+11x+28=0
splitting the middle term
x²+7x+4x+28=0
x(x+7)+4(x+7)=0
(x+4)(x+7)=0
x+4=0 or x+7=0
x= -4 or x= -7
Hence, Correct option is:
c) x= -4 and x= -7